(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Cervical dysplasia, or cervical intraepithelial neoplasia (CIN), is a precancerous condition marked by abnormal cellular changes in the cervical epithelium. The study aims to identify its causes, risk factors, diagnostic approaches, and modern treatment options. Human papillomavirus (HPV) infection is the predominant cause, with other contributing factors such as smoking, immune suppression, and prolonged hormonal contraceptive use. Diagnostic advancements like HPV testing and colposcopy have enhanced early detection rates. Treatment options range from conservative management for low-grade lesions to surgical procedures for advanced cases. Preventive strategies, especially HPV vaccination, show promise in reducing disease prevalence.